PERSELISIHAN HUKUM MODERN DAN HUKUM ADAT DALAM KASUS PENCURIAN SISA PANEN RANDU - Widodo Dwi Putro (Komisi Yudisial RI, 2011)
ABSTRACTModern law and customary law should be able to coexist in a pluralistic constellation of law in Indonesia. But in some cases, modern law deals vis a vis with customary law, and often customary law has to be in yield position. The contradiction has become fact in Batang, Central Java. The case of cotton harvest theft trialed in Batang District Court. Based on the fact, in this paper resolves that the enactment of modern law, often emphasized through legal positivism, tends to hurt the sense of social justice. Positive law or legal positivism not enough to describe fairnes dan justice. Then, jugde, when decides the case, doesn’t use legal positivism only. Keywords: customary law, modern law, legal positivism, social justice ABSTRAKHukum modern dan hukum adat dapat eksis bersama dalam konstelasi hukum Indonesia yang syarat dengan plurarisme. Namun, dalam beberapa kasus harus berhadapan dengan hukum adat seperti putusan atas pencurian batang randu di Batang. Kedua hukum tersebut memiliki tujuan yang sama yaitu keadilan yang jauh melampaui hukum sehingga keadilan tidak bisa sepenuhnya dipastikan dalam rumusan hukum. Hukum tanpa keadilan tidak layak lagi disebut hukum, tetapi keadilan tanpa hukum tetaplah keadilan, meskipun keadilan yang